Pro-fertility effect of Ficus carica fruit extract in streptozotocin-induced male rats - Mat Noor Mahanem; Subramaniam Puvaratnesh; AbuBakar Umarqayum; Shamsusah A Nadia (Asian Pacific Journal of Reproduction)
Objective: To explore the impact of Ficus carica fruit aqueous extract on fertility parameters in streptozotocin (STZ)-induced male rats. Methods: Twenty-four male Sprague-Dawley rats were divided into four different groups. All groups except a normal control group were induced with 50 mg/kg of streptozotocin (STZ) intravenously to induce diabetes. A positive control group was treated with an antidiabetic drug, metformin (500 mg/kg) whereas a negative control group remained untreated throughout the experiment. Meanwhile, another diabetic rat group received treatment with 400 mg/kg of aqueous Ficus carica fruit extract. Rats in the treatment group were administered Ficus carica fruit aqueous extract daily through force-feeding via oral gavage for a 21-day period. Assessments included the sperm quality (count, motility and morphology), histology of the testes, serum testosterone and fasting blood glucose (FBG) level. Results: The FBG level of the Ficus carica-treated rats exhibited a significant decrease compared to the negative control group (P<0.05). Sperm quality analysis also indicated that the aqueous Ficus carica extract had significant positive effects on sperm count and motility (P<0.05). The histology of the testes in Ficus carica- treated rats revealed an improved cell arrangement in the germinal cell layer. Furthermore, serum testosterone level showed an increment in the Ficus carica treatment group in comparison to the negative control group. Conclusions: Our findings provide compelling evidence for the pro-fertility and anti-hyperglycemic properties of aqueous Ficus carica fruit extract in diabetic-induced male rats.